Comparison of multiplex ligation-dependent probe amplification and real-time PCR accuracy for gene copy number quantification using the β-defensin locus. (December 2009) - Perne, Andrea; Zhang, XiangHong; Lehmann, Lutz E.; Groth, Marco; Stuber, Frank; Book, Malte
The reliable quantification of gene copy number variations is a precondition for future investigations regarding their functional relevance. To date, there is no generally accepted gold standard method for copy number quantification, and methods in current use have given inconsistent results in selected cohorts. In this study, we compare two methods for copy number quantification. β-defensin gene copy numbers were determined in parallel in 80 genomic DNA samples by real-time PCR and multiplex ligation-dependent probe amplification (MLPA). The pyrosequencing-based paralog ratio test (PPRT) was used as a standard of comparison in 79 out of 80 samples. Realtime PCR and MPLA results confirmed concordant DEFB4, DEFB103A, and DEFB104A copy numbers within samples. These two methods showed identical results in 32 out of 80 samples; 29 of these 32 samples comprised four or fewer copies. The coefficient of variation of MLPA is lower compared with PCR. In addition, the consistency between MLPA and PPRT is higher than either PCR/MLPA or PCR/PPRT consistency. In summary, these results suggest that MLPA is superior to real-time PCR in β-defensin copy number quantification.